2007
DOI: 10.1128/jvi.02820-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Human Immunodeficiency Virus Type 1 RNase H Primer Grip Enhance 3′-Azido-3′-Deoxythymidine Resistance

Abstract: We recently observed that mutations in the human immunodeficiency type 1 (HIV-1) reverse transcriptase (RT) connection domain significantly increase 3-azido-3-deoxythymidine (AZT) resistance up to 536 times over wildtype (WT) RT in the presence of thymidine analog resistance mutations (TAMs). These mutations also decreased RT template switching, suggesting that they altered the balance between nucleotide excision and template RNA degradation, which in turn increased AZT resistance. Several residues in the HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 28 publications
8
56
0
Order By: Relevance
“…We have previously shown that increases in AZT resistance associated with CN subdomain mutations occur in the presence of TAMs (4,5,19). To first determine if any NRTI resistance was associated with the CN subdomain of AE T1 in the context of its own TAMs-containing POL domain, the POL plus CN subdomain from pHL(AE T1 ) was subcloned into pHL(B-WT) to create AE T1 -AE T1 -B, which was then assayed for AZT resistance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that increases in AZT resistance associated with CN subdomain mutations occur in the presence of TAMs (4,5,19). To first determine if any NRTI resistance was associated with the CN subdomain of AE T1 in the context of its own TAMs-containing POL domain, the POL plus CN subdomain from pHL(AE T1 ) was subcloned into pHL(B-WT) to create AE T1 -AE T1 -B, which was then assayed for AZT resistance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, including recent work by Delviks-Frankenberry et al and Brehm et al (4,11), highlighted the necessity to expand sequencing analysis to include the connection and RNase H subdomains. This contention is further supported by results in this work and by others (16,28,42,43) showing that mutations at the connection subdomain influence susceptibility to some antiretroviral drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in HIV-1 RT that confer resistance to the NRTI, 3Ј-azidothymidine, increase rates of excision (15)(16)(17)(18)(19)(20)(21). More recently, it has been shown that mutations in the connection and RNase H domains of HIV-1 RT confer resistance to NRTIs and NNRTIs (9,10,(22)(23)(24)(25)(26). These mutations appear to exert their effects on susceptibility to 3Ј-azidothymidine more indirectly.…”
Section: Hiv-1mentioning
confidence: 99%